Influence of different extraction methods on the yield and linalool content of the extracts of Eugenia uniflora L. - Galhiane, Mario Sergio [UNESP]; Rissato, Sandra Regina [UNESP]; Chierice, Gilberto O.; Almeida, Marcos V.; Silva, Leticia C. (Elsevier B.V., 2006)
This work has been developed using a sylvestral fruit tree, native to the Brazilian forest, the Eugenia uniflora L., one of the Mirtaceae family. The main goal of the analytical study was focused on extraction methods themselves. The method development pointed to the Clevenger extraction as the best yield in relation to SFE and Soxhlet. The SFE method presented a good yield but showed a big amount of components in the final extract, demonstrating low selectivity. The essential oil extracted was analyzed by GC/FID showing a large range of polarity and boiling point compounds, where linalool, a widely used compound, was identified. Furthermore, an analytical solid phase extraction method was used to clean it up and obtain separated classes of compounds that were fractionated and studied by GC/FlD and GUMS. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Eugenia uniflora L; extraction; gas chromatography; linalool